DIRECTION OF ISLAMIC FINANCE DEVELOPMENT: CHALLENGES AND OPPORTUNITIES IN BANKING - Bahri Sabil; Yusuf Ageng Ariwibowo; Chealshe Oliviana Fega Al Hadid; Aprilia Nur Khasanah; Nisrina Rania Puteri (Department of Islamic Banking, Faculty of Islamic Economics and Business (FEBI), State Islamic University of Sultan Aji Muhammad Idris Samarinda, 2026)
This research aims to analyze the development of Islamic finance during the period 2020–2025 through a bibliometric approach using the OpenAlex database. An initial total of 1,189 documents were selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, yielding 556 articles that met the inclusion criteria. The analysis results show a significant increase in publications concerning Islamic finance, Sharia banking, and Sharia fintech, particularly in 2022 and 2024. Dominant topics include the synergy of Islamic financial institutions, financial technology innovation, financial literacy, and Sharia governance. The co-occurrence network map reveals that the development of Islamic finance is rooted in the interaction between finance, technology, governance, and consumer behavior. Indonesia emerges as a global research hub with major contributions from Islamic higher education institutions. These findings confirm that the integration of digital innovation, Sharia regulation, and public literacy is key to strengthening an inclusive and sustainable Islamic financial ecosystem.